Fertility-sparing treatment of endometrial cancer - is it possible? A case study - Milena Leziak; Klaudia Żak; Małgorzata Satora; Justyna Szpyra; Natalia Kluz; Krzysztof Kułak (Kazimierz Wielki University, 2022)
Background: Endometrial cancer is the most common gynecological malignant neoplasm, which occurs in the majority of cases postmenopausally. The current standard of treatment is surgical - total hysterectomy.  However, it may also occur in younger patients, who are planning pregnancy and want to choose fertility-sparing treatment. For those patients oral high dose progestin therapy with or without hysteroscopic resection should be proposed. It is usually a good option for women with well-differentiated (G1) cancers. For patients with higher grade (G2, G3) or contraindications to progestins, fertility-sparing treatment of endometrial cancer seems impossible. Case report: We present the case of a 34-year old woman diagnosed gynecologically due to abnormal bleeding from the genital tract. Based on USG, she was diagnosed with endometrial polyp. As a treatment, hysteroscopic resection was performed. In the histopathological evaluation G2 endometrial cancer was diagnosed. The standard approach would be a total hysterectomy, but the patient was interested in fertility-sparing options. Due to contraindications to progestins a total hysteroscopic resection was performed counseling the patient about the risks of a novel approach. Histopathology revealed no residual disease and no other lesions during the first year of observations occurred. Conclusion: Total hysteroscopic resection without further progestin therapy may offer the possibility to treat G2 endometrial cancer despite contraindications to the administration of progestins. Our case report should also encourage further evaluation of fertility-sparing management of endometrial cancer with higher than G1 grade.